The prevalence of intraepithelial lesions in preventive examinations carried out in the “legal amazon” region - de Jezus, Sonia Vivian; Masochini, Rosângela Guerino; Cunha, Alan Nogueira da; de Oliveira, Vanessa (Journal of Health & Biological Sciences, 2018)
Introduction: Cervical cancer is a public health problem, and tracking of the disease must follow a set of organized programmed actions, with populations and periodicity defined. Objective: Identifying the prevalence of intraepithelial lesions in preventive examinations performed in the municipality of Sinop- MT between 2010 and 2013. Methods: Statistical data obtained using the DATASUS/SISCOLO system were used. Results: When considering the descriptive diagnosis for cellular alterations, 412 and 167 altered exams with low- and high-grade intraepithelial lesions (respectively) were found. The evalence of both low-grade (25.45%) and high-grade (10.32%) intraepithelial lesions were higher outside of the recommended age range (25-64 years). Conclusions: Studies on the prevention of cervical cancer are extremely relevant in order to analyze the coverage of screening in areas served by basic health units and to understand the factors associated with non-adherence of women to preventive examination. It is noteworthy that during the time period analyzed, women in the municipality of Sinop did not fulfill the municipal goal.